Gaseous exchanges, growth and foliar anatomy of sugarcane plants grown in potassium (K) deprived nutrient solution - Cavalcante, Valéria Santos [UNESP]; Prado, Renato de Mello [UNESP]; de Almeida, Hilário Júnior [UNESP]; Cruz, Flávio José Rodrigues [UNESP]; dos Santos, Durvalina Maria Mathias [UNESP] (My University, 2015)
Potassium participates in the plant metabolism and has an important effect on stomata opening, the activation of some enzymes and the mobilization of solutes, with positive effects on photosynthate distribution. Thus, in order to verify the effects of potassium absence on plant gaseous exchanges, growth and leaf anatomy of the sugarcane, an experiment was carried out under greenhouse conditions. The experiment was conducted for 90 days in a greenhouse with nutrient solution, where treatments consisted of the presence (control) and absence of K. The experiment was setup in a completely randomized design with ten repetitions. Gaseous exchanges were evaluated together with plant growth, chloroplast ultrastructure of the diagnostic leaf, chlorophylls content, green color index, total soluble sugars content, starch content, and K accumulation in the plant. Sugarcane plants grown in K-deprived nutrient solutions showed reductions in transpiration (-35%), photosynthesis (-58%), stomatal conductance (-32%), chlorophylls contents a (-25%) and b (-29%), green color index (-76%), plant height (-22%), tiller diameter (-23%), root density (-53%), K accumulation in the shoots (-76%) and roots (-79%), and dry matter mass of the shoots (-22%) and roots (-23%). The total soluble sugars content (26%) and starch content (28%) in the leaves increased, as well as the intercellular concentration of CO2 (40%). Sugarcane in the absence of K showed reduced growth due to the influence of this nutrient on gaseous exchanges and alterations in leaf anatomy, suggesting greater focus should be taken on potassium nutrition, mainly in physiological terms, since there are vast agricultural areas with potassium deficiency around the world.
Keywords: Dry matter; Nutrient; Photosynthesis; Saccharum spp; Sugars; Transpiration